Money Can't Buy Me Trust: Evidence of Exogenous Influences Crowding out Process‐based Trust in Alliances. (13th September 2016) - Christoffersen, Jeppe; Robson, Matthew J.
Abstract : In this study we investigate how external interventions shape process‐based trust development in cross‐border alliances. Specifically, we exploit a unique opportunity to observe the magnitude of external intervention through publicly available amounts of money given by the foreign, developed country partners' government to support alliances with local, developing country partners. Applying motivation crowding theory to trust processes, we develop theoretical logic explaining how and under what conditions such third‐party financial support negatively affects the local partner's trust. Our assertions were tested using archival and survey data on 105 international strategic alliances. We find that amount of support is detrimental to local partner trust but that the negative relationship can be dampened via interaction between partners and agreement throughout these interactions. This shows a need for partners to think through trust development consequences of external interventions during the setting up of their alliances, in order to be able to act in a manner which promotes trust.